2015
DOI: 10.1016/j.abb.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 1B1: An unexpected modulator of liver fatty acid homeostasis

Abstract: Cytochrome P450 1b1 (Cyp1b1) expression is absent in mouse hepatocytes, but present in liver endothelia and activated stellate cells. Increased expression during adipogenesis suggests a role of Cyp1b1 metabolism in fatty acid homeostasis. Wild-type C57BL/6j (WT) and Cyp1b1-null (Cyp1b1-ko) mice were provided low or high fat diets (LFD and HFD, respectively). Cyp1b1-deletion suppressed HFD-induced obesity, improved glucose tolerance and prevented liver steatosis. Suppression of lipid droplets in sinusoidal hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(88 citation statements)
references
References 96 publications
(133 reference statements)
5
83
0
Order By: Relevance
“…We operationally define DIO as an increase in body weight (BW) and adiposity in mice on the HFD relative to equivalent mice on the LFD [29, 30]. GVAD-HFD decreased DIO and liver weight (Figure 2C, D, and F).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We operationally define DIO as an increase in body weight (BW) and adiposity in mice on the HFD relative to equivalent mice on the LFD [29, 30]. GVAD-HFD decreased DIO and liver weight (Figure 2C, D, and F).…”
Section: Resultsmentioning
confidence: 99%
“…Selections of previously reported liver gene responses to the BD-HFD compared to an approximately isocaloric low fat diet (LFD) were used in comparative analyses [29, 30]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently microarray data from the livers of the CYP1B1 KO mice that are resistant to diet-induced obesity indicated that CYP1B1 deletion substantially alters the expression of genes associated with fatty acid homeostasis [33]. Several studies have examined the relationship between individual CYP1B1 polymorphisms and cancer risk [14,15,[34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%